Evaluation of a population mobility, mortality, and birth surveillance system in South Kivu, Democratic Republic of the Congo - Jarrett, Prudence (Disasters, 2019)
Prospective, community‐based surveillance systems for measuring birth, death, and population movement rates may have advantages over the ‘gold‐standard’ retrospective household survey in humanitarian contexts. A community‐based, monthly surveillance system was established in South Kivu, Democratic Republic of the Congo, in partnership with a local implementing partner and the national ministry of health. Data were collected on the occurrence of births, deaths, arrivals, and departures over the course of one year, and a retrospective survey was conducted at the end of the period to validate the information. Discrepancies between the two approaches were resolved by a third visit to the households with discordant records. The study found that the surveillance system was superior in terms of its specificity and sensitivity in measuring crude mortality and birth rates as compared to the survey, demonstrating the method's potential to measure accurately important population‐level health metrics in an insecure setting in a timely, community‐acceptable manner.